The use of UTAUT model to understand user intention and user behavior of mobile banking BIMA PT Bank Jateng - Christophorus Bagus Ratnanto Putro; Maria Apsari Sugiat (Goodwood Publishing, 2025)
Purpose: This study explores factors influencing users’ behavioral intention and actual usage of the BIMA mobile banking application by PT Bank Jateng. It applies the Unified Theory of Acceptance and Use of Technology (UTAUT), enhanced with contextual variables such as mobile self-efficacy, perceived enjoyment, and satisfaction. Research/methodology: A quantitative approach was conducted through a survey of 384 BIMA users. Data were analyzed with Structural Equation Modeling (SEM) using SmartPLS. Reliability and validity were tested with AVE and Composite Reliability, while model fit was assessed through SRMR, NFI, R², and Q² values. Results: Of 13 hypothesized paths, 10 were supported. Mobile self-efficacy strongly affected perceived enjoyment, which significantly influenced performance expectancy, effort expectancy, and satisfaction. Satisfaction emerged as the most influential factor on intention to use, which in turn impacted usage behavior. Social influence and facilitating conditions also contributed positively. However, performance expectancy did not significantly affect satisfaction, and both effort expectancy and facilitating conditions showed no significant effect on intention to use. Conclusions: Emotional factors like enjoyment and satisfaction, together with social influence, dominate over functional aspects in shaping adoption and continued use of mobile banking, suggesting a shift toward user experience-driven digital banking strategies. Limitations: The study is limited to one application, cross-sectional design, and PLS-SEM, reducing broader generalization. Contribution: This research extends UTAUT by incorporating emotional and contextual variables, providing practical insights for enhancing user experience and digital adoption in regional banking.